Calibrating Doppler Imaging of Preterm Intracerebral Circulation Using a Microvessel Flow Phantom - Camfferman, Fleur A.; Ecury-Goossen, Ginette M.; La Roche, Jhuresy E.; de Jong, Nico; van ’t Leven, Willem; Vos, Hendrik J.; Verweij, Martin D.; Nasserinejad, Kazem; Cools, Filip; Govaert, Paul; Dudink, Jeroen (Frontiers in Human Neuroscience, 2015)
Introduction. Preterm infants are born during critical stages of brain development, in which the adaptive capacity of the fetus to extra-uterine environment is limited. Inadequate brain perfusion has been directly linked to preterm brain damage. Advanced high-frequency ultrasound probes and processing algorithms allow visualization of microvessels and depiction of regional variation. To assess whether visualization and flow velocity estimates of preterm cerebral perfusion using Doppler techniques is accurate, we conducted an in vitro experiment using a microvessel flow phantom. Materials and Methods. An in-house developed flow phantom containing two microvessels (inner diameter 200 and 700 microns) with attached syringe pumps, filled with blood-mimicking fluid, was used to generate non-pulsatile perfusion of variable flow. Measurements were performed using an Esaote MyLab70 scanner. Results. Microvessel mimicking catheters with velocities as low as 1cm/sec were adequately visualized with a linear ultrasound probe. With a convex probe velocities <2 cm/sec could not be depicted. Within settings, velocity and diameter measurements were highly reproducible (intra class correlation 0.997 (95% CI 0.996-0.998) and 0.914 (0.864-0.946)). Overall, mean velocity was overestimated up to 3-fold, especially in high velocity ranges. Significant differences were seen in velocity measurements when using steer angle correction and in vessel diameter estimation (p<0.05). Conclusion. Visualization of microvessel size catheters mimicking small brain vessels is feasible. Reproducible velocity and diameter results can be obtained, although important overestimation of the values is observed. Before velocity estimates of microcirculation can find its use in clinical practice, calibration of the ultrasound machine for any specific Doppler purpose is essential. The ultimate goal is to develop a sonographic tool that can be used for objective study of regional perfusion in routine practice.